The Mechanism and Pathways of Dopamine and Dopamine Agonists in Prolactinomas - Liu, Xiaoshuang; Tang, Chao; Wen, Guodao; Zhong, Chunyu; Yang, Jin; Zhu, Junhao; Ma, Chiyuan (Frontiers in Endocrinology, 2019)
Dopamine agonists such as bromocriptine and cabergoline are the predominant treatment drugs for prolactinoma by inhibiting prolactin secretion and shrinking tumor size. However, the pathways of either dopamine or its agonists that lead to the death of cells are incompletely understood and some are even conflicting conclusions. The main aim of this paper is to review the different pathways of dopamine and its agonists in prolactinomas to help to gain a better understanding of their functions and drug resistance mechanisms.